MSME Empowerment Management through the E-Peken Program in an Effort to Improve the Local Economy in Surabaya - Nayla Ratu Meihani; Ferlintang Naya Ridha Nayla; Rizma Aulia; Keyza Zana Sabitha Zayyan; Meirinawati Meirinawati; Trenda Aktiva Oktariyanda (Income Journal Of Economics Development, 2026)
The E-Peken (Electronic-Based Village Economic Empowerment) program is one of the breakthroughs from the Surabaya City Government to strengthen the community's economy through the use of digital in MSMEs. The purpose of this study is to examine the management of MSME empowerment carried out through the E-Peken program by applying the management theory of Henri Fayol which includes the planning, organization, implementation, and supervision stages. The object of this research is the management of the E-Peken program as an innovation of the Surabaya City Government in supporting digital-based MSME empowerment, and the research was conducted in Surabaya City, East Java, Indonesia. The research approach applied is qualitative descriptive with literature studies, where information is obtained from journals, articles, official government news, policy documents, and publications related to the E-Peken program. The study used secondary data with document review guidelines, data classification tables, and analysis instruments based on the POAC management functions. Data were analyzed using qualitative descriptive analysis through the stages of data reduction, data presentation, and conclusion drawing. The findings of the study indicate that the E-Peken program has been running quite effectively in terms of planning, organizing, implementation, and supervising. This initiative has succeeded in helping MSMEs in increasing market access through digital media. However, during its implementation, there are several obstacles, such as a lack of technological understanding among MSME actors, uneven internet access, and lack of consistency in the use of the platform. For this reason, improvements in digital training, infrastructure strengthening, and routine evaluation are needed so that the program can run more efficiently and optimally.